Possibilidades e limites para diversidade de interações sobre política partidária em blogs - Wang, Maria Auxiliadora de Lima (2013)
Based on the principle of operant selection, it is possible to assume that certain verbal practices in a community tend to be initially diverse and over the time become less diverse. Aiming to investigate this assumption, in this study the verbal interactions on the blogs of the journalists Luis Nassif (LN) and Ricardo Kotscho (RK) were analyzed. The goal was to identify aspects of the interaction between participants and of the opinions about the target political issue that could be characterized as diversity and uniformity. A post related to the Brazilian political parties PSDB and PT published, at first, in the blog of Kotscho and, after that, re-posted in the blog of Nassif, as well as comments on the post, served as data for the analysis. All comments published in both blogs were analyzed according to three main aspects: (1) positioning and form of interaction between the participants (classified as agreement/disagreement, among other categories, and classified according to how the participants presented their opinions, that is, with or without arguments); (2) positioning and form of interaction about PSDB / PT(classified as favorable or unfavorable to these political parties, and classified with respect to how the arguments were presented, that is, citing aspects / strategies of the party s political program, or disqualifying the political party / politician belonging to the party; (3) positioning and form of interaction about the orientation of the media in political coverage (classified as favorable or unfavorable to PSDB / PT, and classified according to how the participants described the media coverage, that is, with criticisms / disqualifications addressed to media companies / journalists in general, or with criticisms / disqualifications addressed to specific media companies/journalists). Diversity in many aspects of interactions between participants was found in both blogs. Regarding interactions about politics, uniformity was found in LN s blog: the majority of the participants positioned favorably to PT and unfavorably to PSDB. In RK s blog, the relationship between favorable and unfavorable positioning to PSDB / PT was more balanced, although with the largest number of participants positioned themselves unfavorably to the PSDB compared to the number of the participants that positioned themselves unfavorable to PT. Based on these results and from the results of other research in which interactions in the LN s blog were analyzed, it is possible that the behavior of the group in LN s blog has gone / is going through a selection process, resulting in a more uniform political orientation of its members. Possibilities and limits to diversity / uniformity of verbal interactions on web are discussed, as well, possibilities and limits to planning potential interventions for changes in cultural practices widely disseminated